Investigating Biotic Interactions in Deep Time. (January 2021) - Fraser, Danielle; Soul, Laura C.; Tóth, Anikó B.; Balk, Meghan A.; Eronen, Jussi T.; Pineda-Munoz, Silvia; Shupinski, Alexandria B.; Villaseñor, Amelia; Barr, W. Andrew; Behrensmeyer, Anna K.; Du, Andrew; Faith, J. Tyler; et al.
Abstract : Recent renewed interest in using fossil data to understand how biotic interactions have shaped the evolution of life is challenging the widely held assumption that long-term climate changes are the primary drivers of biodiversity change. New approaches go beyond traditional richness and co-occurrence studies to explicitly model biotic interactions using data on fossil and modern biodiversity. Important developments in three primary areas of research include analysis of (i) macroevolutionary rates, (ii) the impacts of and recovery from extinction events, and (iii) how humans ( Homo sapiens ) affected interactions among non-human species. We present multiple lines of evidence for an important and measurable role of biotic interactions in shaping the evolution of communities and lineages on long timescales. Highlights: Challenging the widespread perspective that long-term diversity patterns are shaped primarily by climate is not possible without using fossil record data to understand the role of biotic interactions. Important recent development and application of models that utilize data of both living and extinct species have enabled analyses to move beyond simply excluding potential abiotic drivers to explicitly modeling biotic drivers for the first time. Analyses of paleontological data show that biotic interactions shape the temporal diversity trajectories and rates of origination and extinction for numerous taxa. Extinction of keystone species has disproportionate impacts on biotic interactions among surviving species. Recovery from extinction events can be sped up or slowed down by biotic interactions among surviving species. Historically, humans ( Homo sapiens ) have acted as large, generalist predators, disrupting interaction networks among non-human species.